A hundred years of theological training in the Apostolic Faith Mission of South Africa - M. Nel (Acta Theologica)
The AFM started as an interracial mission with a strong emphasis on the “anointing of the Holy Spirit” and the ministry of each member of the assembly. Leadership was developed through the local church as the body of Christ and there were no distinctions between clergy and laity. All who were saved were expected (and trained) to witness; no theological training was required for the different levels of ministry, not even for preachers. There was a hierarchy starting with church members being witnesses, but with the opportunity to develop into a deacon, elder, local preacher, and finally an overseer. In this article the development of training for the ministry along separate lines for different racial groups in accordance with the ruling Apartheid policy of the Nationalist government is discussed. After a hundred years the AFM has one training structure with a new centralized seminary and one curriculum for all.